Correlation between cubic-based polymorphic phase boundary structures and the piezoelectric properties of 0.96(Na0.5K0.5)(Nb1-xSbx)-0.04BaTiO3 ceramics. Issue 4 (1st October 2020) - Ma, Xing-Hua; Zhang, Zhenlu; Xu, Tiewei; Zhang, Shuling
ABSTRACT: CuO-added 0.96(Na0.5 K0.5 )(Nb1- x Sb x )-0.04BaTiO3 ceramics with 0.0 ≤  x ≤ 0.1 were sintered at 980°C for 6 hours and the effects of antimony on the successive phase transition and the corresponding piezoelectric properties were carefully studied. It was found that with the increasing of x values, the crystal structures varied from orthorhombic-tetragonal polymorphic phase boundary (PPB), orthorhombic-tetragonal-cubic PPB, and finally to the tetragonal-cubic PPB structure. Accordingly, the piezoelectric properties of the specimens were influenced by the varied crystal structures. In particular, the specimen with a tetragonal (88.01%)-cubic (11.99%) PPB structure ( x = 0.06) showed a large d 33 of 302 pC/N and a high strain of 0.17% at 4.5kV/mm, revealing its promising potential as the Pb-free piezoelectric actuators.